2009
DOI: 10.1104/pp.109.136531
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Gene Encoding the Iron-Sulfur Subunit of Mitochondrial Complex II Is Regulated by B3 Domain Transcription Factors during Seed Development in Arabidopsis    

Abstract: Mitochondrial complex II (succinate dehydrogenase) is part of the tricarboxylic acid cycle and the respiratory chain. Three nuclear genes encode its essential iron-sulfur subunit in Arabidopsis (Arabidopsis thaliana). One of them, SUCCINATE DEHYDROGENASE2-3 (SDH2-3), is specifically expressed in the embryo during seed maturation, suggesting that SDH2-3 may have a role as the complex II iron-sulfur subunit during embryo maturation and/or germination. Here, we present data demonstrating that three abscisic acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…Finally, it is interesting to note that although neither malate nor fumarate exert their effects on stomata by affecting ABA, the phytohormone could, conditionally, act upstream of the organic acids, given that a recent study in Arabidopsis revealed the SDH2-3 gene to be upregulated by ABA. 98 It will be important to establish the functional significance of this observation in future studies. Further genetic, molecular biological and biochemical analyses will be required to identify other components of the signal transduction pathway(s) and the corresponding effectors that are involved in the stomatal responses in order to obtain a deeper understanding of the biochemical mechanisms and the precise factors and environmental cues underlying this phenomenon.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Finally, it is interesting to note that although neither malate nor fumarate exert their effects on stomata by affecting ABA, the phytohormone could, conditionally, act upstream of the organic acids, given that a recent study in Arabidopsis revealed the SDH2-3 gene to be upregulated by ABA. 98 It will be important to establish the functional significance of this observation in future studies. Further genetic, molecular biological and biochemical analyses will be required to identify other components of the signal transduction pathway(s) and the corresponding effectors that are involved in the stomatal responses in order to obtain a deeper understanding of the biochemical mechanisms and the precise factors and environmental cues underlying this phenomenon.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…For example, a detailed study on the regulation of COX5b-1 revealed AP2/ERF, ABF4, bZIP and trihelix transcription factors as involved in the transcriptional regulation of COX5b-1 (Comelli et al 2012). Three B3 domain transcription factors (ABI3, FUS3 and LEAFY COTYLE-DON2) have also been shown to regulate the expression of the iron-sulphur subunit of complex II during seed development in Arabidopsis (Roschzttardtz et al 2009). Analysis of the promoters of nuclear genes encoding mitochondrial proteins reveals an enrichment of elements called site II (Gonzalez et al 2007), that have been subsequently shown to play a key role in the regulation of a variety of nuclear genes encoding mitochondrial proteins.…”
Section: Biogenesis: Transcriptional and Post-transcriptional Controlmentioning
confidence: 99%
“…In plants, complex II has been demonstrated to contain four additional subunits (Eubel et al, 2003;Millar et al, 2004); however, no clear biological function of these additional subunits has been described. Moreover, in contrast with the situation for complexes I, III, and IV, for which multiple gene functional analyses have allowed direct evaluation of the physiological functions of their constituent subunits (Newton et al, 1990;Marienfeld and Newton, 1994;Pla et al, 1995;Howad and Kempken, 1997;Dutilleul et al, 2005;Vidal et al, 2007), as yet only two forward or reverse genetic strategies have been employed to study the function of complex II in plants (Leó n et al, 2007;Roschzttardtz et al, 2009). These studies revealed that disruption of the expression of the SDH1-1 gene results in alterations in gametophyte development, pollen abortion, and reduced seed set (Leó n et al, 2007) and that the absence of SDH2-3 in Arabidopsis thaliana seeds appears to slow their germination (Roschzttardtz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in contrast with the situation for complexes I, III, and IV, for which multiple gene functional analyses have allowed direct evaluation of the physiological functions of their constituent subunits (Newton et al, 1990;Marienfeld and Newton, 1994;Pla et al, 1995;Howad and Kempken, 1997;Dutilleul et al, 2005;Vidal et al, 2007), as yet only two forward or reverse genetic strategies have been employed to study the function of complex II in plants (Leó n et al, 2007;Roschzttardtz et al, 2009). These studies revealed that disruption of the expression of the SDH1-1 gene results in alterations in gametophyte development, pollen abortion, and reduced seed set (Leó n et al, 2007) and that the absence of SDH2-3 in Arabidopsis thaliana seeds appears to slow their germination (Roschzttardtz et al, 2009). Furthermore, again by contrast with the other complexes of the inner mitochondrial membrane (see for example, Millar et al, 1993;Raghavendra et al, 1994;Sweetlove et al, 2002;Garmier et al, 2008), relatively few specific inhibitors of this complex have been found (Miyadera et al, 2003;Horsefield et al, 2006;Mogi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%